The Dynamics of Self‐Esteem in Partner Relationships. Issue 2 (March 2015) - Mund, Marcus; Finn, Christine; Hagemeyer, Birk; Zimmermann, Julia; Neyer, Franz J.
Abstract: Previous research on the role of self‐esteem in partner relationships indicates that it is both predictive of and predicted by variables such as relationship satisfaction. However, most of these studies were constrained to only relationship satisfaction, cross‐sectional or individual data. In the present study, we examine the dynamic interplay between self‐esteem and both broad (i.e. relationship satisfaction) and specific aspects of relationship quality (independence and connectedness) reflecting the fulfilment of agentic and communal needs in stable partner relationships from both an intrapersonal perspective and an interpersonal perspective. Study 1 assessed 186 individuals at three measurement occasions over 15 years and suggests a common developmental dynamic between self‐esteem and relationship satisfaction, as indicated by initial correlations and correlated changes. In Study 2, actor and partner effects in stable couples ( N = 2124 dyads) were examined over a period of three years. It was found that self‐esteem and all three aspects of relationship quality are dynamically intertwined in such a way that both previous levels and changes in one domain predict later changes in the other domain. Together, the findings indicate that self‐esteem is consequential for the development of a variety of relationship aspects but likewise influenced by these very aspects. Copyright © 2015 European Association of Personality Psychology